KELEMBAGAAN PENDIDIKAN : PENDIDIKAN INFORMAL, NONFORMAL DAN FORMAL - Abdullah (STIT AL-ISHLAH BONDOWOSO, 2018)
One or the culture that can be used to instill human values which is also called character education value is informal, informal, and formal education institution. Formal education which is often called schooling education, in the form of series of educational levels that have been standardized such as elementary, junior high school, and universities. Formal education is more focused on providing skills or skills to prepare learners to jump into the community. Non-formal education is a mechanism that provides an opportunity for everyone to enrich science and technology through lifelong learning. Informal education is every opportunity where there are regular and targeted communication outside the school such as family environment and community environment. The method used is the literature study method (from books obtained, from private libraries and from the internet). The lessons in school both theoretical and practical lessons will be of great benefit to the development of the individual within the informal and informal environment. In social interaction, the individual must have ethics and manners. To get this polite and ethical learning starts from an informal education in the family. The purpose of the above description is clear that learning obtained from an individual not only comes from an educational environment, but from the three educational environments so that between the other premises mutually refine and eventually will produce an idial education or in other terms will produce a perfect human (perfect human being useful for nation and religion).